Building Trust Through Clarity: The Role of Key Audit Matters in Enhancing Financial Reporting Integrity for State-Owned Construction Companies (BUMN Karya) - Belinda, Vania; Suyanto, Suyanto (The Indonesian Journal of Accounting Research, 2025)
This study explores the application and effectiveness of Key Audit Matters (KAMs) in improving financial transparency and audit quality within Indonesia's state-owned construction enterprises (BUMN Karya). A qualitative content analysis methodology was applied to identify recurring themes and trends, linking audit procedures to the risks highlighted in KAM disclosures. The study reveals that KAM disclosures play a critical role in providing stakeholders with insights into complex financial risks, particularly in large-scale infrastructure projects, including asset impairment and recoverability, revenue recognition and contract fulfillment, and valuation and estimation. Furthermore, the analysis shows that auditors undertake procedures to examine management's assumptions, verify compliance with Indonesian Financial Reporting Standards (PSAK), and minimize the risk of material misstatements. However, inconsistencies in the identification and reporting of KAMs, along with limited guidelines, pose challenges for auditors. This research provides valuable insights into the application of KAMs within Indonesia's public enterprises, offering a deeper understanding of how audit procedures address financial reporting challenges. This study contributes to the growing body of knowledge on KAM disclosures, focusing on the unique challenges faced by Indonesia's state-owned construction enterprises. By analyzing the implementation of KAMs in this context, it offers insights into the relationship between audit procedures, transparency, and stakeholder trust, advancing the literature on auditing practices in emerging economies.